Fabrication of naturel pumice/hydroxyapatite composite for biomedical engineering - OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN; SALMAN, SERDAR (BMC, 2016)
Background: We evaluated the Bovine hydroxyapatite (BHA) structure. BHA powder was admixed with 5 and 10 wt% natural pumice (NP). Compression strength, Vickers micro hardness, Fourier transform infrared spectroscopy, scanning electron microscopy (SEM) and X-ray diffraction studies were performed on the final NP-BHA composite products. The cells proliferation was investigated by MTT assay and SEM. Furthermore, the antimicrobial activity of NP-BHA samples was interrogated. Results: Variances in the sintering temperature (for 5 wt% NP composites) between 1000 and 1300 degrees C, reveal about 700 % increase in the microhardness (similar to 100 and 775 HV, respectively). Composites prepared at 1300 degrees C demonstrate the greatest compression strength with comparable result for 5 wt% NP content (87 MPa), which are significantly better than those for 10 wt% and those that do not include any NP (below 60 MPa, respectively). Conclusion: The results suggested the optimal parameters for the preparation of NP-BHA composites with increased mechanical properties and biocompatibility. Changes in micro-hardness and compression strength can be tailored by the tuning the NP concentration and sintering temperature. NP-BHA composites have demonstrated a remarkable potential for biomedical engineering applications such as bone graft and implant.
Keywords: Bioceramics; Natural pumice; Bovine hydroxyapatite; Bioinspired composites; GLASS-REINFORCED HYDROXYAPATITE; THERMAL-DECOMPOSITION; MECHANICAL-PROPERTIES; TRICALCIUM PHOSPHATE; BONE; PUMICE; MICROSTRUCTURE; DENSITY; APATITE; MGO